Facilitating collective action and enhancing local knowledge: a herbal medicine case study in Talaandig communities, Philippines - Hartanto, Herlina; Valmores, Cecil (International Food Policy Research Institute, 2006)
The indigenous people of Talaanding in Basac village, Bukidnon, the Philippines, had to deal with a high occurrence of disease and a high number of malnourished children in their village. This situation was due to the inability of the local health clinic to provide adequate health service and medicine to the community. Using an approach that promotes social learning and collective action, a CIFOR Adaptive Collaborative Management (ACM) research team facilitated a group of women, mostly the village health workers, in addressing their local health problems by using their local knowledge of medicinal plants and herbal medicines. This paper describes the ACM concept and the social learning processes that the women went through in identifying their health-related problems in the village, devising strategies to deal with those problems, monitoring the outcomes of their action, and improving their subsequent strategies. This paper also shows that the ACM processes promoted not only collective action and social learning among the women, but also helps to revive local knowledge of herbal medicines and conserve genetic resources in the area. The sustainability of the women’s efforts will depend on their ability to mobilize more community members to manage the established herb gardens, to enforce rules so that the costs and benefits of the gardens can be shared more equally, to link-up with local government and other stakeholders, and to continuously learn and adapt their management strategies.